Place Matters: Variation in the Black/White Very Preterm Birth Rate Across U.S. Metropolitan Areas, 2002–2004 - Kramer, Michael R. (Association of Schools of Public Health, 2008)
OBJECTIVE. We reported on the distribution of very preterm (VPT) birth rates by race across metropolitan statistical areas (MSAs). METHODS. Rates of singleton VPT birth for non-Hispanic white, non-Hispanic black, and Hispanic women were calculated with National Center for Health Statistics 2002–2004 natality files for infants in 168 MSAs. Subanalysis included stratification by parity, age, smoking, maternal education, metropolitan size, region, proportion of MSA that was black, proportion of black population living below the poverty line, and indices of residential segregation. RESULTS. The mean metropolitan-level VPT birth rate was 12.3, 34.8, and 15.7 per 1,000 live births for white, black, and Hispanic women, respectively. There was virtually no overlap in the white and black distributions. The variation in mean risk across cities was three times greater for black women compared with white women. The threefold disparity in mean rate, and two- to threefold increased variation as indicated by standard deviation, was maintained in all subanalyses. CONCLUSION. Compared with white women, black women have three times the mean VPT birth risk, as well as three times the variance in city-level rates. The racial disparity in VPT birth rates was composed of characteristics that were constant across MSAs, as well as factors that varied by MSA. The increased sensitivity to place for black women was unexplained by measured maternal and metropolitan factors. Understanding determinants of differences in both the mean risk and the variation of risk among black and white women may contribute to reducing the disparity in risk between races.